Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Cimaju Utama Kreasindo Indonesia di Kota Bogor - Wijayanti, Agnes Luviani; Wijayanti, Kiki Dwi (Jurnal Manajemen & Pendidikan [JUMANDIK], 2024)
The aim of this research is to determine the influence of motivation and work discipline on employee performance at PT Cimaju Utama Kreasindo Indonesia in Bogor City. The method used is quantitative. The sampling technique used saturated sampling, namely 55 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that motivation has a significant effect on employee performance with a coefficient of determination value of 53.5% and the hypothesis test obtained t count > t table or (7.802 > 2.006). Work discipline has a significant effect on employee performance with a coefficient of determination value of 43.2% and hypothesis testing obtained t count > t table or (6.349 > 2.006). Motivation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 7.662 + 0.432X1 + 0.373X2. The coefficient of determination value is 64.1% while the remaining 37.5% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (46.428 > 2.780).